Microstates, Entropy and Quanta An Introduction to Statistical Mechanics - Koks, Don (Springer International Publishing, 2018)
Statistical mechanics: the bane of many a physics student. But when pared back to its underlying concepts and built from the ground up, the field takes on a charm of its own, and embraces a wide variety of physical phenomena. This book presents a straightforward introduction to the key concepts in statistical mechanics, following the popular style of the author's highly successful textbook "Explorations in Mathematical Physics". Offering a clear, conceptual approach to the subject matter, the book presents a treatment that is mathematically complete, while remaining very accessible to undergraduates. It commences by showcasing the counting of configurations, which leads to entropy, thermodynamics, and physical chemistry. The Boltzmann and Maxwell distributions then appear, with related topics of thermal conductivity and viscosity. Next come bosons via Einstein's and Debye's theories of heat capacity, and fermions via electrical conduction and low-temperature heat capacity of metals. The text ends with a derivation of blackbody radiation, and uses this to discuss the greenhouse effect, cosmology, and lasers. Suitable for use with core undergraduate courses in statistical mechanics and thermodynamics, this book concentrates on using solid mathematics, while avoiding cumbersome notation. All mathematical steps are included in the text and worked examples. About the Author Don Koks studied at the University of Auckland in the 1980s, where he obtained a Bachelor of Science in pure and applied mathematics and physics, and a Master of Science in applied accelerator physics. He was awarded a doctorate in quantum cosmology (quantum statistics and black hole theory) by Adelaide University. He works in Australian Defence, specialising in relativistic precision timing, orbital mechanics, spatial orientation concepts, and radar signal processing. Review of Explorations in Mathematical Physics by Don Koks "With enjoyable and sometimes surprising excursions along the way, the journey provides a fresh look at many familiar topics, as it takes us from basic linear mathematics to general relativity... look forward to having your geometric intuition nourished and expanded by the author's intelligent commentaries." Eugen Merzbacher, University of North Carolina.